Local Political Dynamics And Prabowo-Gibran Campaign Strategy In The 2024 Presidential Election In Surabaya City Contestation Analysis Discourse - Steinly Suwanto Putra; Darsono Darsono; Triana Dianita Handayani (Jurnal Mamangan, 2024)
This study aims to analyze Dynamics of Local Politics and Prabowo-Gibran Campaign Strategy in the 2024 Presidential Election in Surabaya City. Analysis of Discourse Contestation. This study uses a qualitative approach with a descriptive-critical type of research, aiming to describe how the Prabowo-Gibran campaign strategy is articulated as a hegemonic practice in the public space of Surabaya city, as well as how dominant discourses are produced, circulated, and accepted by the public. The data collection technique in this study uses a qualitative approach with an exploratory strategy. This study shows that the campaign of the Prabowo Subianto-Gibran Rakabuming Raka pair in the 2024 Presidential Election can not only be understood as a conventional electoral process, but as a hegemonic articulation project that successfully unites various discursive elements—including symbols, programs, figures, and political networks—in one dominant political representation block. This campaign strategy successfully constructs a chain of equivalences between demands for the welfare of the common people, youth aspirations, loyalty to Jokowi, and the logic of national development in one coherent populist and affective narrative. The main thesis of this research can be formulated that the Prabowo-Gibran campaign in the 2024 Presidential Election is a form of hegemonic articulation structured through affective, visual, and symbolic strategies, which combine Jokowi's legitimacy, digital populism symbols, and formal and informal electoral networks, in order to form a new political formation compatible with the post-Jokowi order.